Portret Nowego Dziennikarstwa w reportażach Huntera S. Thompsona - Żyrek-Horodyska, Edyta (Załącznik Kulturoznawczy, 2021)
The main purpose of this article is to present the key features of the New Journalism outlined in Hunter S. Thompson’s reportages. The research is focused on such texts as Hell’s Angels, Fear and Loathing in Las Vegas and The Kentucky Derby Is Decadent and Depraved. In these reportages the reader can find reflections related to the journalist’s profession. The American reporter repeatedly confronts ‘the old press’ with the ways of working typical for ‘the new journalists’. According to Thompson, the New Journalism is immersive, full of emotional tone, subjective, focused on details. It uses the techniques typical for literary forms.